2023
DOI: 10.3390/children10121912
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Simple and Complex Appendicitis in Children and the Potential Correlation to Common Viral Pathogens—A Retrospective Cohort Study between 2010 and 2019 in The Netherlands

Sarah-May M. L. The,
Paul van Amstel,
Sophie M. Noordzij
et al.

Abstract: The aim of this study was to evaluate the annual, seasonal and monthly trends in children with simple and complex appendicitis and their correlation to common viral pathogens in the Netherlands. A consecutive multicenter retrospective cohort study was performed between 2010 and 2019 including children (<18 years) surgically treated for appendicitis. The primary outcome was the distribution of children with simple and complex appendicitis per year, season and month. Relevant seasonal variation was defined as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…This is further corroborated by a study of 1711 appendicitis cases, where the presence of lymphoid tissue hyperplasia was only observed in 15 cases [98]. A virus can induce lymphoid hyperplasia, but a recent multicenter retrospective cohort study in children showed no correlation between AA and common viral pathogens [99].…”
Section: Discussionmentioning
confidence: 58%
“…This is further corroborated by a study of 1711 appendicitis cases, where the presence of lymphoid tissue hyperplasia was only observed in 15 cases [98]. A virus can induce lymphoid hyperplasia, but a recent multicenter retrospective cohort study in children showed no correlation between AA and common viral pathogens [99].…”
Section: Discussionmentioning
confidence: 58%